Transformational Leadership as a Source of Participatory Governance - D. O. Kutsenko (Управленческое консультирование, 2020)
The purpose of this article is to justify the new role of the municipal official, i.e. the role of a transformation leader, whose activity is increasingly connected with the introduction of participatory governance, with the development of citizen participation and through this participation, progressive changes in the local community and the municipality as a whole. The method of research was theoretical analysis of foreign experience in the use of social technologies at the local level, which made it possible to form a theoretical model of transformational leadership. The formation of such a model is important from the point of view of developing key competencies of municipal officials in the near future. Empirical support for the theoretical analysis was obtained through content analysis of documents published on the website of the Governor of St. Petersburg (https://www. gov.spb.ru/governor). The research made it possible to conclude that transformational leadership behavior of municipal authorities is aimed at increasing the participatory nature of governance, the mission of valence in the ratio of clear and attractive development priorities at the municipal, regional and federal levels with the interests of local communities. The constant need to solve new social and political problems and contradictions by municipal leaders means a continuous search for a balance between efficiency and fairness, and the effectiveness of this balance depends on the transformational potential of municipal managers. The participatory style of municipal management implies that transformation leaders use social technologies for public participation in state and municipal management. Transformational leadership is based on the principles of democracy, efficiency, effectiveness, openness, rule of law, ethics, competence, innovation, sustainability, performance, and accountability. It makes it possible to replenish the deficit of public resources, which is increasing due to economic crises, as well as unjustified and excessive expansion of social services and the number of their recipients. Transformative leadership involves reaching consensus among different social groups, finding a balance between economic rationality and social justice, between extensive growth and environmentally friendly sustainable development. This becomes the main task of any level of government, primarily the municipal government as the closest to the place where problems arise and the search for optimal solutions.